Adaptive PCM Pattern Synchronization - Van de Houten, R. S. (International Foundation for Telemetering, 1967)
International Telemetering Conference Proceedings / October 02-04, 1967 / Marriott Motor Hotel, Washington, D.C. === The trend toward more automated PCM decommutation systems demands less operator intervention in their operation. A weak link in this progression has been in the implementation of group synchronizer strategy. A new synchronizer has been developed based on the optimum properties of sequential probability ratio testing which requires only one program based on required worst case decision error probabilities and which is independent of the PCM format being synchronized. A mathematical model is formulated which accurately describes the operating characteristics of this technique. These operating characteristics are then compared to conventional synchronizer characteristics which demonstrate the superiority of this approach. The decision process described inherently adapts to signal conditions by making decisions faster and with less chance of error as bit error rate decreases. Only the Check Mode is discussed, but the same techniques apply to the Lock Mode.